2011
DOI: 10.1210/me.2010-0366
|View full text |Cite
|
Sign up to set email alerts
|

Luteinizing Hormone Receptor mRNA Down-Regulation Is Mediated through ERK-Dependent Induction of RNA Binding Protein

Abstract: The ligand-induced down-regulation of LH receptor (LHR) expression in the ovaries, at least in part, is regulated by a posttranscriptional process mediated by a specific LH receptor mRNA binding protein (LRBP). The LH-mediated signaling pathways involved in this process were examined in primary cultures of human granulosa cells. Treatment with 10 IU human chorionic gonadotropin (hCG) for 12 h resulted in the down-regulation of LHR mRNA expression while producing an increase in LHR mRNA binding to LRBP as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 49 publications
2
22
0
1
Order By: Relevance
“…Our previous studies have established that LRBP is a key component of the post-transcriptional mechanism of LH receptor expression by causing accelerated degradation of LHR mRNA during LHR downregulation [21,22]. The present findings extend this by demonstrating that inhibition of eIF5A hypusination by GC7 reduces the binding of LHR mRNA to LRBP as presented in Fig.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our previous studies have established that LRBP is a key component of the post-transcriptional mechanism of LH receptor expression by causing accelerated degradation of LHR mRNA during LHR downregulation [21,22]. The present findings extend this by demonstrating that inhibition of eIF5A hypusination by GC7 reduces the binding of LHR mRNA to LRBP as presented in Fig.…”
Section: Discussionsupporting
confidence: 87%
“…We have previously shown that LH/hCG-activated cAMP/PKA/ERK1/2 signaling plays an important role in LHR downregulation by increasing LRBP expression [21]. The present study extends this further showing that this pathway is also instrumental in increasing the hypusination of eIF5A.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Notably, Nair and Menon [11] and Wang and Menon [12] found that Mvk binds to LHR mRNA, resulting in a reduction of LHR mRNA levels by increasing the instability of the transcript [11,12]. They also clarified the fact that the protein kinase A (PKA)-dependent extracellular signal-related kinase (ERK) signaling pathway, activated by LHR stimulation, controls Mvk protein levels, thereby down-regulating LHR mRNA [34]. However, the molecular processes responsible for the down-regulation of LHR mRNA have not yet been defined in detail.…”
Section: Discussionmentioning
confidence: 96%
“…The fold change in gene expression was calculated using the ΔΔCt method with 18S rRNA as the internal control, as described previously [14]. …”
Section: Methodsmentioning
confidence: 99%